La femme à travers les yeux d'un uraniste - Torre Giménez, Estrella de la (Verbum – Analecta Neolatina, 2013)
Surrounded by women since his childhood, the uranian Eekhoud never excluded them from his life or his literary work. A motherless child early in his life, some women became veritable accomplices, including his grandmother, his great aunt and his wife Cornélie, and he in turn gave women a privileged role in his novels, in many of which they are the protagonists. Through his fictional heroines he manages to convey his true feelings, his critique of the bourgeoise complacency, and his attitudes toward anything he loved or abhorred. The female figure became for him the driving force between his true nature and a society of which he was aware he was an outcast.